Alwerakah and Alwarrakoon, and their intellectual and educational impact from the beginning of islam until the sixth century AH in Iraq and the Islamic Levant - Mohamdy, Hamed; Al-Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2022)
Alwarrakoon and the art, profession or craft of alwerakah are important and exciting elements for every researcher to delve into research and follow up on its scientific and intellectual impact; This is because it is closely related to writing, reading, blogging and research, which is the basis of the work of any researcher or student, and from here came this study or research, which consists of two sections, each of which has three demands, through which the researcher followed the impact of That profession, then he went on to discuss the factors of the emergence of Alwerakah as an independent profession and the contribution of some of its pioneers and the use of Alwerakah in important matters in the history of Islamic civilization, such as writing the Qur’an and transcribing hadiths, and then the beginning of the blogging movement in Arab Islamic history, and its development in the Rashidun, Umayyad and then Abbasid eras, which witnessed a major support for Alwerakah , which is the establishment of the city of Baghdad and then the House of Wisdom, to begin what the researcher calls the golden age of Alwerakah scientifically, intellectually and professionally. The intellectual that was raised by Alwerakah at that time, is the main reason of what we have today as a sources, books and encyclopedias which taught us in a various sciences and knowledge. In general, this research follows Alwerakah and the results that affected it, from its beginning until golden age of the Abbasid era.